Kontribusi Nyata Mahasiswa Kkn Uinsi dalam Program Keagamaan di Kelurahan Teritip - Janna, As‟sadyah Tul; Fauzi, M. Haki Qouli; Dila, Anisa Ratna; Assidiq, Muhamad Bagus; Rahmahtiah, Aulia; linda, Nur; Rahmah, Siti (TAFANI: Jurnal Pengabdian Masyarakat, 2024)
This service scientific article entitled "The Real Contribution of UINSI KKN Students in Religious Programs in Teritip Subdistrict" is a form of service carried out by 7 students from different faculties, namely the Sharia Faculty, Tarbiah and Teacher Training Faculty, Islamic Economics and Business Faculty and Ushuluddin Faculty Adab and Da'wah. This service activity emphasizes religious programs for 42 days, starting from July 13 to August 23 2023. In this scientific journal article, UINSI KKN uses a qualitative approach with descriptive methods. The data collection process involves direct field observation and describing KKN activities or programs that have been implemented in Teritip Village.